Site Selection Analysis for Grouper Culture in Floating Cage Using GIS-Based Weighted Linear Combination Analysis in Kulisusu Bay - Dwiputra, Mohammad Ashari; Kurnia, Rahmat; Riani, Etty (Journal of Science and Applicative Technology, 2024)
Land suitability evaluation is a crucial component that supports the sustainable development of aquaculture. One economically valuable commodity in this field is the grouper fish. Kulisusu Bay, located in North Buton Regency, is an area with potential for grouper culture in floating cages. The objective of this research is to analyze the suitability of the land in Kulisusu Bay for floating cage aquaculture of grouper. The study begins by identifying key parameters that directly affect the success of aquaculture activities. These parameters include primary and secondary data that are used to build spatial data. Subsequently, a spatial model is constructed based on this data, resulting in a spatial database. Each parameter is then weighted and scored. The final step involves spatial overlay modeling, where the weighted and scored results are used to generate a land suitability map. The research results show that a significant portion of 2,253 hectares is highly suitable, with an additional 810 hectares being suitable for the activity. These areas are primarily concentrated in the central region of Teluk Kulisusu. Based on these findings, it can be concluded that the waters of Teluk Kulisusu have great potential for the development of grouper culture in floating cages. However, the support of various stakeholders, including the government, is necessary to ensure that this aquaculture activity is sustainable by implementing environmentally friendly culture practices.